2019
DOI: 10.1130/g45678.1
|View full text |Cite
|
Sign up to set email alerts
|

Jurassic carbonatite and alkaline magmatism in the Ivrea zone (European Alps) related to the breakup of Pangea

Abstract: We report on pipe-like bodies and dikes of carbonate rocks related to sodic alkaline intrusions and amphibole mantle peridotites in the Ivrea zone (European Southern Alps). The carbonate rocks have bulk trace-element concentrations typical of low-rare earth element carbonatites interpreted as cumulates of carbonatite melts. Faintly zoned zircons from these carbonate rocks contain calcite inclusions and have trace-element compositions akin to those of carbonatite zircons. Laser ablation-inductively coupled plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
4
17
0
Order By: Relevance
“…These authors reported TIMS zircon ages at ~200 Ma from lower crustal pyroxenites and dunites that they interpreted as a distal and deep expression of the Central Atlantic Magmatic Province. A Jurassic age of emplacement (LA-ICP-MS concordant age of 187 ±2.4 and 192 ±2.4 Ma, see Figure 2) has been recently reported also for carbonatite bodies and dykes by Galli et al, [59] that they linked to sodic CO2-bearing melts derived from an amphibole-rich mantle source. In particular, Hf values indicates a moderate crustal assimilation during emplacement of carbonatitic magma [59].…”
Section: Geological Setting and Geochronological Backgroundsupporting
confidence: 80%
See 2 more Smart Citations
“…These authors reported TIMS zircon ages at ~200 Ma from lower crustal pyroxenites and dunites that they interpreted as a distal and deep expression of the Central Atlantic Magmatic Province. A Jurassic age of emplacement (LA-ICP-MS concordant age of 187 ±2.4 and 192 ±2.4 Ma, see Figure 2) has been recently reported also for carbonatite bodies and dykes by Galli et al, [59] that they linked to sodic CO2-bearing melts derived from an amphibole-rich mantle source. In particular, Hf values indicates a moderate crustal assimilation during emplacement of carbonatitic magma [59].…”
Section: Geological Setting and Geochronological Backgroundsupporting
confidence: 80%
“…By comparing zircons from dykes studied in this work and from other Triassic-Jurassic intrusive bodies of IVZ it is evident that studied zircon grains are characterised by M-HREE contents significantly higher than those documented in zircons from leucocratic dykes, locally corundumbearing, in the Finero Complex (northern IVZ; [14,22]) and carbonatites (central IVZ; [59]). The zircons in both felsic dykes are characterized by pronounced negative Eu anomalies that can be absent in the other local Mesozoic intrusions (Figure 9b).…”
Section: Zircon Isotopic and Chemical Datamentioning
confidence: 69%
See 1 more Smart Citation
“…Vavra et al 1996 ; Vavra and Schaltegger 1999 ). In the Ivrea Zone, sporadic intrusions are dated in the Triassic (granitic dikes at 251 ± 2 Ma, Wright and Shervais 1980 ; the Finero Mafic Complex at 232 ± 3 Ma, Zanetti et al 2013 ; and syenite dikes 225 ± 13 Ma, Stähle et al 1990 ), alkaline pegmatoids at the Triassic-Jurassic boundary (210–190 Ma, Oppizzi and Schaltegger 1999 ; Schaltegger et al 2008 ; 2011 ) and carbonate rocks related to sodic alkaline intrusions and amphibole mantle peridotites in the early Jurassic (187 ± 2.4 and 192 ± 2.5 Ma, Galli et al 2019 ). This further supports a high geothermal gradient and circulation of fluids in the middle to lower crust of the Sesia and Ivrea zones between ~ 250 and 190 Ma, also enhanced by the intense deformation affecting these domains in the Triassic and the Jurassic (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Cassinis & Zezza, 1982;Pamić, 1984;Vaccaro et al 1991;Laurenzi et al 1994;Visonà & Zanferrari, 2000;Stähle et al 2001;Liberi et al 2011;Zanetti et al 2013;Beltràn-Triviño et al 2016;Storck et al 2019), with minor pulses at about 215-220 Ma (e.g. Stähle et al 2001;Cassinis et al 2008;Casetta et al 2019) and 192-187 Ma (Galli et al 2019). However, U-Pb zircon ages of the deep crustal intrusions from Finero (e.g.…”
Section: D2 Triassic Magmatism As An Early Stage Of Pangea Break-upmentioning
confidence: 99%